O efeito da música na dor e ansiedade em pacientes submetidos a procedimentos cardíacos percutâneos : uma revisão sistemática com metanálise - Santana, Joyce Francielle Nei Bomfim de (2018)
Introduction: Cardiovascular diseases are the leading causes of death in the world. Included in this group, ischemic heart disease (IHD) is more frequent and responsible for high morbidity and mortality rates. Last two decades, a significant progress had happened to the recognition, management and treatment in patients with IHD, which determined a meaningful reduction in death rates, infarctions and recurrent ischemias. Despite technological advancement is increasing and its use of contemporary techniques, pain and anxiety cause a series of physiological repercussions that may impair the quality of clinical outcomes. Objectives: This study focused on identify in literature the music effect to pain, anxiety and hemodynamic parameters before and after percutaneous cardiac procedures. Method: This is a systematic review with meta-analysis that followed all recommendations of the Cochrane Collaboration and the verification items recommended by the tool Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA), as well as based on the Assessing the tool Methodological Quality of Systematic Reviews (AMSTAR). Results: 40 papers were found on a initial research, and 11 of them filled the inclusion criteria. These papers showed music is effective to reduce anxiety and hemodynamic parameters, and it was also confirmed in the meta-analysis which identified a meta-analytic estimate of difference among the average rates of 4.02 (95% HF: 2.48 to 6.68), even though it was chosen by the researcher. However, its effects on pain were inconclusive, which was also shown in the meta-analysis that identified a non-significant meta-analytic estimate of -0.01 (95% HF: -0.36 to 0.32) when VAS was used, although there is still a necessity for forthcoming studies. Due to the variability of genres and time of musical exposure, it was not possible to determine which music or for how long are the ideal to achieve more positive results on the outcomes of interest, but, it may presume soft, slow beats and instrumental songs show better results. Regarding how to execute it, the use of headphones is recommended as it allows the patient to focus its attention on the musical stimulus. Most of the studies obtained good methodological quality and low risk of bias. Whereas meta-analysis identified risk of publication bias for studies about anxiety. Conclusion: That systematic review identified music is effective to reduce anxiety and hemodynamic parameters. Nonetheless the results were inconclusive in order to determine association in pain reduction. These results may be useful in the development of recommendations for use of music in interventional cardiology.